Thyroid hormone profile in preeclampsia patients: a case control study - Nii Ayite Aryee; Kwame Adu-Bonsaffoh; Benjamin Arko-Boham; Osbourne Quaye; Hope Asazu; Emmanuel Tagoe (Gynecological Endocrinology, 2023)
Objective: Preeclamptic women are reported to have a higher incidence of thyroid dysfunction that correlates with the severity of preeclampsia. The aim of this study was to assess thyroid hormone profiles in in pregnant women with preeclampsia and gestational hypertension and the risk for thyroid dysfunction.Methods: In this study, age-matched pregnant females in the second trimester of pregnancy, diagnosed with preeclampsia (PE), gestational hypertension (GH), as cases, and apparently healthy normotensive (NT) pregnant woman as controls were recruited. Blood samples were drawn for the assessment of thyroid hormone (TSH, FT3 and FT4) levels and thyroid dysfunction.Results: Out of the total of 133 pregnant women recruited for this study, sub-clinical hypothyroidism was the only thyroid dysfunction common to all study groups, with a prevalence of 3.3% in both PE and NT groups, and 4.3% in the GH group. 1% of women in the PE group had sub-clinical hyperthyroidism, compared to 3.3% in the NT group. Although TSH and FT3 were elevated in normotensives, mean differences between the three groups were not statistically significant. However, mean FT4 levels in the GH group (12.99 ± 1.24) and PE group (12.33 ± 2.26), when compared to the control group (11.55 ± 1.94), were significantly higher (p < 0.05).Conclusion: Undiagnosed subclinical hypothyroidism was found in all the categories of pregnant women studied, which if uncontrolled, could increase the risk of pregnancy-related complications, especially in pregnant women with preeclampsia and gestational hypertension.